Prepreg manufacturing method and the like

JP2025032704AActive Publication Date: 2025-03-12ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023138135
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-03-12
Estimated Expiration
2043-08-28

AI Technical Summary

Benefits of technology

【0010】 本開示によれば、100℃未満の環境下で長期間に亘り、優れた誘電特性を維持したガラスクロスを用いた、プリプレグの製造方法を提供することができる。 また、本開示は、プリント配線基板用の上記プリプレグを製造する、プリント配線基板用のプリプレグの製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032704000001
    Figure 2025032704000001
  • Figure 2025032704000002
    Figure 2025032704000002
Patent Text Reader

Abstract

To provide a prepreg manufacturing method that utilizes glass cloth, which can maintain excellent dielectric properties over a long period under an environment below 100°C.SOLUTION: A prepreg manufacturing method comprises a step of impregnating glass cloth with a resin composition and producing a prepreg. The glass cloth used is stored under conditions satisfying the conditional formula (a), (Tdp-14)×D≤1500 (where Tdp is the dew point under the atmospheric pressure in the storage environment, and D is the days stored), and has a dielectric loss tangent at 10 GHz of 0.00200 or less after the storage.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a prepreg. [Background technology]

[0002] Currently, the performance of information terminals such as smartphones is improving, and high-speed communication, as typified by 5G communication, is progressing. Against this background, for example, for printed wiring boards for high-speed communication, not only is there a demand for improved heat resistance, but also for further improvement in the dielectric properties of the insulating material (for example, reduction in dielectric tangent). Similarly, there is a demand for improved dielectric properties for prepregs used as insulating materials for printed wiring boards. Here, the prepregs are produced through a process of impregnating glass cloth with a resin composition. Therefore, there is a demand for improved dielectric properties for the glass cloth used in the production of the prepregs, and also for the cured product of the resin composition used in the production of the prepregs.

[0003] As a means for improving the dielectric properties, for example, a method of producing a prepreg using low dielectric glass is known (see Patent Documents 1 and 2). Specifically, Patent Document 1 discloses a method of producing a prepreg using silicon dioxide (SiO 2 ) preparing a prepreg using glass yarns with a composition amount of 98 to 100 mass %, and Patent Document 2 describes heat treating a quartz glass cloth.

[0004] In addition, the Si-OH group on the surface of quartz glass is highly active, and when it absorbs moisture through hydrogen bonds, especially in a high-temperature atmosphere, the Si-O-Si bond is cleaved to generate Si-OH groups (SiO 2 +H 2It is known that the Si-OH groups formed by the reaction of Si-OH with Si-O-Si bonds deteriorate the dielectric tangent of the glass cloth (see, for example, paragraph

[0006] of Patent Document 3). Patent Document 3 discloses a method for recombining Si-OH groups to form Si-O-Si bonds, thereby lowering the dielectric tangent of the glass cloth. This method involves placing the quartz glass cloth in a heating furnace and heating it in a vacuum or in a gas with a dew point of 15°C or less under conditions where the maximum heating temperature is 100 to 600°C and the heating amount, expressed as "heating temperature (°C) of 100°C or more" x "heating time (h)", is 450 (°C·h) or more. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2018-127747 A [Patent Document 2] Patent Publication No. 2021-63320 [Patent Document 3] Patent No. 7269416 Summary of the Invention [Problem to be solved by the invention]

[0006] Conventionally, it has been believed that water does not contribute to lowering the dielectric tangent of glass cloth in the temperature range below 100°C. This is because of the equilibrium reaction (SiO 2 +H 2 This is also supported by the disclosure regarding the reaction between Si-OH groups (O⇔Si-OH) that "below 100°C, the activation energy in the reaction between Si-OH groups is insufficient, so the amount of Si-OH groups does not decrease and the dielectric tangent does not decrease either." (Patent Document 3, paragraph 0025).

[0007] However, the present inventors have found for the first time that even if the dielectric tangent of the glass cloth during production is reduced by the means disclosed in Patent Documents 1 to 3, when the glass cloth is stored for a long period of time, the generation of silanol groups due to the above-mentioned equilibrium reaction progresses even in an environment of less than 100° C., and the dielectric tangent of the glass cloth increases.

[0008] Therefore, an object of the present disclosure is to provide a method for producing a prepreg using a glass cloth that maintains excellent dielectric properties for a long period of time in an environment of less than 100°C. Another object of the present disclosure is to provide a method for producing a prepreg for a printed wiring board, which produces the above prepreg for a printed wiring board. [Means for solving the problem]

[0009] [1] A method for producing a prepreg, comprising the steps of impregnating a glass cloth with a resin composition and producing a prepreg, The glass cloth may include The following condition (a): (Tdp-14) × D ≦ 1500 (a) (In the formula, Tdp is the dew point under the atmospheric pressure of the storage environment, and D is the number of days of storage.) and the glass cloth has a dielectric loss tangent of 0.00200 or less at 10 GHz after storage. A method for producing prepreg. [2] The glass cloth has glass yarns containing a plurality of filaments as warp yarns and weft yarns, The silicon (Si) content in the glass yarn is silicon dioxide (SiO 2 2. The method for producing a prepreg according to Item 1, wherein the content of the carbon black is 95.0 to 100 mass % in terms of carbon black content. [3] The glass cloth may be The following condition (b): (Tdp-8)×D ≦800 (b) 3. The method for producing a prepreg according to item 1 or 2, wherein the prepreg is produced using the glass cloth stored under conditions that satisfy the above. [4] The glass cloth may be The following condition (c): (Tdp-2)×D ≦800 (c) 4. The method for producing a prepreg according to Item 3, wherein the prepreg is produced using the glass cloth stored under conditions that satisfy the above. [5] The glass cloth may be The following condition (d): (Tdp-(-4))×D ≦1500 ···(d) 5. The method for producing a prepreg according to Item 4, wherein the prepreg is produced using the glass cloth stored under conditions that satisfy the above. [6] The following conditions (i) and (ii): (i) heating and degreasing the glass cloth at a temperature of 600 to 1500° C. for a time of 10 minutes or less; and (ii) a step of degreasing the glass cloth by heating at a temperature of 300° C. or more and less than 600° C. for 24 hours or more in an atmosphere having a dew point temperature of 15° C. or less under atmospheric pressure; 6. The method for producing a prepreg according to any one of items 1 to 5, wherein the prepreg is produced using the glass cloth that has been subjected to thermal deoiling based on at least one of the above and then stored. [7] The following formula (1): X(R) 3-n SiY n (1) (In the formula, X is a group having at least one of an amino group and an unsaturated double bond group having radical reactivity, each Y is independently an alkoxy group, n is an integer of 1 to 3, and each R is independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group.) 7. A method for producing a prepreg according to any one of items 1 to 6, comprising producing the prepreg using the glass cloth that has been surface-treated with a surface treatment agent containing the silane coupling agent represented by the formula: [8] 8. The method for producing a prepreg according to any one of items 1 to 7, wherein a cured product of the resin composition has a dielectric loss tangent of 0.0025 or less at 10 GHz. [9] 9. The method for producing a prepreg according to any one of items 1 to 8, wherein the resin composition contains at least one resin selected from the group consisting of epoxy resins, allylated epoxy resins, maleimide resins, bismaleimide resins, cyanate resins, cyclopentadiene-styrene copolymer resins, polyphenylene ethers, polyether ether ketones, polyether ketones, polyether sulfones, and fluororesins.

[10] 10. The method for producing a prepreg according to any one of items 1 to 9, wherein the resin composition contains at least one of inorganic particles and a crosslinking agent.

[11] The glass cloth may be 11. The method for producing a prepreg according to any one of items 1 to 10, wherein the glass cloth has a dielectric loss tangent of 0.00200 or less at 10 GHz both before and after storage under conditions that satisfy the conditional formula (a).

[12] The glass cloth may be 12. The method for producing a prepreg according to any one of items 1 to 11, wherein the glass cloth has a rate of change in dielectric tangent before and after storage {dielectric tangent at 10 GHz after storage under conditions satisfying the conditional formula (a) / dielectric tangent at 10 GHz before storage under conditions satisfying the conditional formula (a)} of 180% or less.

[13] 13. The method for producing a prepreg according to any one of items 1 to 12, further comprising a step of heating and drying the glass cloth impregnated with a resin composition.

[14] 14. A method for producing a prepreg for a printed wiring board, comprising producing the prepreg according to any one of items 1 to 13 for a printed wiring board. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide a method for producing a prepreg using a glass cloth that maintains excellent dielectric properties for a long period of time in an environment of less than 100°C. The present disclosure can also provide a method for producing a prepreg for a printed wiring board, which produces the above prepreg for a printed wiring board. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present disclosure (hereinafter, referred to as the present embodiment) will be described. The present invention is not limited to the present embodiment, and can be implemented in various modifications without departing from the scope of the present invention.

[0012] In this specification, various measurements are performed based on the methods described in the Examples unless otherwise specified. In this specification, the upper or lower limit of a numerical range described in a stepwise manner may be replaced with the upper or lower limit of a corresponding numerical range described in another stepwise manner, and may further be replaced with the corresponding value described in the Examples. In this specification, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the function of the step is achieved.

[0013] [Prepreg manufacturing method] One aspect of the present embodiment is a method for producing a prepreg. The method for producing a prepreg includes a step of impregnating a glass cloth with a resin composition and producing a prepreg, The glass cloth may be The following condition (a): (Tdp-14) × D ≦ 1500 (a) (In the formula, Tdp is the dew point under the atmospheric pressure of the storage environment, and D is the number of days of storage.) and the glass cloth has a dielectric loss tangent of 0.00200 or less at 10 GHz after storage. A method for producing prepreg. According to this method, it is possible to provide a method for producing a prepreg using a glass cloth that maintains excellent dielectric properties for a long period of time in an environment of less than 100°C.

[0014] It has been generally recognized that in the temperature range below 100°C, the reaction in which the Si-O-Si bond on the glass surface is cleaved by moisture to generate Si-OH groups is not activated. Therefore, those skilled in the art have not come up with the idea of ​​solving the problem of the dielectric tangent of glass cloth increasing over time while it is stored in such a temperature range, and therefore, no particular consideration or investigation has been given to a method for solving this problem (for example, a method for storing glass cloth). As a result, there have been cases in which prepregs are produced using glass cloth with an increased dielectric tangent.

[0015] In this regard, by setting the storage conditions of the glass cloth before prepreg production (glass cloth for prepreg production) to the range of formula (a), it is possible to suppress the cleavage of Si-O-Si bonds due to moisture present in the storage environment during the storage period, and thus the generation of Si-OH groups, and therefore it is possible to produce a prepreg with good dielectric properties using the glass cloth before the dielectric loss tangent of the glass cloth deteriorates significantly. In the present disclosure, the "storage environment" refers to the atmosphere (gas) that the glass cloth comes into direct contact with. In addition, in the present disclosure, "suppression" refers to reducing the occurrence of an event and the degree of its increase, etc. For example, "suppression" of the dielectric loss tangent does not mean that the dielectric loss tangent does not increase at all, but it is sufficient that the increase in the dielectric loss tangent is limited to a certain extent.

[0016] The above-mentioned production method is, for example, A step of storing the glass cloth so that the storage environment cumulative value {(Tdp-14)×D} satisfies the above range (storage step); and a step of impregnating a glass cloth with a resin composition while the storage environment cumulative value satisfies the above range (resin impregnation step); may include. The above manufacturing method is as follows: a step of heating and drying the glass cloth impregnated with the resin composition (heating and drying step); The present invention may further include:

[0017] <Storage process> In the storage step, the glass cloth is stored so that the storage environment cumulative value {(Tdp-14)×D} satisfies the above range. The method of controlling the dew point and the method of controlling the number of days of storage will be described later.

[0018] <Resin varnish for prepregs> The resin composition used in this embodiment may be prepared as a varnish (a state in which the resin composition is dissolved and / or uniformly dispersed in a solvent) from the viewpoint of improving the impregnation into the glass cloth and from the viewpoint of ease of handling.

[0019] The solvent used for preparing the varnish is preferably one that can dissolve and / or disperse the resin composition and can be evaporated at a temperature at which the composition is maintained in an uncured or semi-cured state. Examples of the solvent include organic solvents having a boiling point of 50 to 200°C, preferably 80 to 150°C. Specific examples of the solvent include hydrocarbon non-polar solvents such as toluene, xylene, hexane, and heptane; and hydrocarbon polar solvents such as ethers and esters. For organic resins that are difficult to dissolve in solvents, it is also possible to use them as aqueous dispersions with a surfactant and water. The amount of the solvent used may be an amount that can dissolve and disperse the resin composition and impregnate the obtained solvent or dispersion into glass cloth. The amount of the solvent used is, for example, preferably 10 to 200 parts by mass, more preferably 20 to 100 parts by mass, relative to 100 parts by mass of the resin composition.

[0020] <Resin impregnation process> In the resin impregnation step, the glass cloth is impregnated with the resin composition in a state where the cumulative storage environment value satisfies the above range. impregnating a glass cloth with the varnish; The impregnation is carried out by the method described above. As the impregnation method, a known method may be used, for example, immersion, coating, film lamination, etc. Impregnation can be repeated multiple times as necessary. In this case, it is also possible to adjust the composition and impregnation amount to the final desired one by repeating the impregnation using multiple resin compositions with different compositions and concentrations.

[0021] <Heat drying process> In the heat drying step, the glass cloth impregnated with the resin composition is heated and dried in a drying oven, thereby volatilizing the solvent. The glass cloth impregnated with the varnish may be heated in the drying oven at preferably 50 to 150°C, more preferably 60 to 120°C. The drying time is, for example, 1 to 10 minutes. This makes it easy to suitably remove the solvent. In the case of an aqueous dispersion, it is preferable to further heat at 300 to 400°C for 5 minutes to 1 hour in order to remove the surfactant.

[0022] <Glass cloth> The glass cloth has glass yarns containing a plurality of glass filaments as warp and weft, and in particular has a structure in which the glass yarns are woven as warp and weft. Examples of the weaving structure of the glass cloth include plain weave, lattice weave, satin weave, and twill weave, and among these, the plain weave structure is preferable. In this embodiment, the measurement period of the storage environment cumulative value (i.e., the period including the storage period of the glass cloth until the prepreg is manufactured using the glass cloth) is assumed to be relatively long. Therefore, in this embodiment, whichever weaving structure is adopted, it is affected by the storage to the same extent, and such a difference in weaving structure is treated as not affecting the measurement of the storage environment cumulative value.

[0023] The weaving density of the warp and weft yarns constituting the glass cloth is preferably 10 to 120 yarns / inch (=10 to 120 yarns / 25 mm), more preferably 40 to 100 yarns / inch. If the weaving density is within the above range, a glass cloth having a preferred thickness is easily obtained. The weaving densities of the warp and weft yarns may be different from each other.

[0024] The weight of the glass cloth (mass of the glass cloth) is preferably 8 to 250 g / m 2 , more preferably 8 to 100 g / m 2 , and more preferably 8 to 80 g / m 2 , and particularly preferably 8 to 50 g / m 2 When the basis weight of the glass cloth is within the above range, a glass cloth having a preferable thickness is easily obtained.

[0025] The thickness of the glass cloth is preferably 60 μm or less, more preferably 55 μm or less, and even more preferably 50 μm or less. If the thickness of the glass cloth is within the above range, it is easy to obtain a glass cloth suitable as an insulating material. The thickness of the glass cloth may be more than 0, 5 μm or more, or 10 μm or more.

[0026] The dielectric loss tangent of the glass cloth is measured by the method described in the Examples. In this embodiment, the dielectric loss tangent at 10 GHz after the above storage is 0.00200 or less. The dielectric loss tangent of the glass cloth having a dielectric loss tangent of 0.00200 or less at 10 GHz increases over time due to the influence of moisture in the storage environment at a temperature of less than 100°C. However, the increase in the dielectric loss tangent of the glass cloth can be suitably suppressed by controlling the storage conditions of the glass cloth within the range of the above formula (a).

[0027] The dielectric loss tangent at 10 GHz of the glass cloth (glass cloth after the above storage) is preferably 0.00160 or less, more preferably 0.00120 or less, even more preferably 0.00090 or less, still more preferably 0.00070 or less, particularly preferably 0.00050 or less, and particularly preferably 0.00040 or less. Glass cloth having a dielectric loss tangent within the above range is easily affected by moisture around the glass cloth in the storage environment, and therefore the effect of suppressing an increase in the dielectric loss tangent is easily obtained.

[0028] Here, it is preferable to use a glass cloth having a dielectric loss tangent of 0.00200 or less at 10 GHz both before and after the storage. This makes it easier to obtain the effects of this embodiment. From the same viewpoint, both before and after the storage, the dielectric loss tangent of the glass cloth at 10 GHz is preferably 0.00160 or less, more preferably 0.00120 or less, even more preferably 0.00090 or less, still more preferably 0.00070 or less, particularly preferably 0.00050 or less, and particularly preferably 0.00040 or less.

[0029] Also, as glass cloth, It is preferable to use the glass cloth in which the rate of change in dielectric tangent before and after storage (dielectric tangent at 10 GHz after storage under conditions satisfying condition (a) / dielectric tangent at 10 GHz before storage under conditions satisfying condition (a)) is 180% or less or 170% or less, which makes it easier to obtain the effects of this embodiment.

[0030] Glass Thread The glass yarn constituting the glass cloth is preferably obtained by using low dielectric glass as a raw material. Such glass yarn has a silicon (Si) content of SiO 2 It is more preferable that the Si content is 95.0 to 100 mass% in terms of the total mass. By using such glass yarn, it is easy to improve the dielectric properties of the obtained glass cloth (for example, reduce the dielectric tangent). In addition, since the dielectric tangent of the glass cloth is likely to increase significantly over time in such glass yarn, the effect of suppressing the increase in the dielectric tangent is easily obtained by applying this embodiment to an embodiment using such glass yarn. From the viewpoint of easily improving the dielectric properties, the Si content is preferably 99.0 mass% or more, more preferably 99.5 mass% or more, and even more preferably 99.9 mass% or more. By having the silicon content within the above range, the number of Si-O-Si bonds in the glass yarn tends to be large, and therefore the effect of this embodiment is easily obtained.

[0031] The average filament diameter of the glass filaments constituting the glass yarn is preferably 2.5 to 9.0 μm, more preferably 2.5 to 7.5 μm, even more preferably 3.5 to 7.0 μm, still more preferably 3.5 to 6.0 μm, and particularly preferably 3.5 to 5.5 μm. When the filament diameter is equal to or greater than the lower limit, the filament breaking strength is easily ensured, and fluff is less likely to occur in the resulting glass cloth. When the filament diameter is less than the upper limit, the mass of the glass cloth is prevented from becoming too large, and therefore the glass cloth is easily transported or processed.

[0032] <Silane coupling agent> The glass cloth preferably has a surface treatment agent containing a silane coupling agent on its surface. Preferably, the glass yarn (including glass filament) constituting the glass cloth is surface-treated with a surface treatment agent containing a silane coupling agent. When the glass cloth has a surface treatment agent, the reactivity with the matrix resin tends to be improved when producing a prepreg. In addition, the glass cloth is less susceptible to the influence of moisture during storage, so that an increase in the dielectric tangent over time can be more effectively suppressed.

[0033] The surface treatment agent is, for example, a compound represented by the following formula (1): X(R) 3-n SiY n (1) In the formula, X is a group having at least one of an amino group and an unsaturated double bond group having radical reactivity, each Y is independently an alkoxy group, n is an integer of 1 to 3, and each R is independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group. In other words, the prepreg is preferably produced using glass cloth that has been surface-treated with the above-mentioned surface treatment agent and then stored.

[0034] From the viewpoint of excellent reactivity with the matrix resin, the above X is more preferably an organic functional group having one or more methacryloxy groups or acryloxy groups. The alkoxy group for Y is preferably an alkoxy group having 1 to 5 carbon atoms (having a carbon number of 1, 2, 3, 4 or 5) from the viewpoint of facilitating stable treatment of the glass cloth.

[0035] As a surface treatment agent, the silane coupling agent shown in formula (1) may be used alone or in a mixture of two or more silane coupling agents having different X in formula (1). In addition, as the silane coupling agent shown in formula (1), for example, vinyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, 5-hexenyltrimethoxysilane, etc. may be used alone or as a mixture thereof.

[0036] The molecular weight of the silane coupling agent is preferably 100 to 600, more preferably 150 to 500, and even more preferably 200 to 450. In particular, it is preferable to use two or more silane coupling agents having different molecular weights. By treating the glass fiber surface with two or more silane coupling agents having different molecular weights, the density of the treatment agent on the glass surface tends to be increased, and therefore the reactivity with the matrix resin tends to be further improved.

[0037] From the viewpoint of not inhibiting reactivity with resin, the silane coupling agent is preferably non-ionic. Among non-ionic silane coupling agents, silane coupling agents having at least one group selected from the group consisting of vinyl group, methacryloxy group, and acryloxy group are preferred, and silane coupling agents having at least one methacryloxy group or acryloxy group are more preferred. Since the reactivity with resin is not inhibited, the heat resistance and reliability of the resulting printed wiring board are easily improved.

[0038] Loss on ignition The ignition loss value of the glass cloth is preferably 0.01% by mass or more and less than 2.0% by mass, more preferably 0.01% by mass or more and less than 1.5% by mass, even more preferably 0.02% by mass or more and less than 1.0% by mass, even more preferably 0.03% by mass or more and less than 0.8% by mass, and particularly preferably 0.03% by mass or more and less than 0.3% by mass. When the ignition loss value is within the above range, it is easy to obtain a glass cloth with a reduced dielectric tangent. The ignition loss value is measured in accordance with JIS R3420.

[0039] [storage] <Cumulative values ​​of storage environment> In the present embodiment, the method for producing a prepreg is characterized in that a dew point under atmospheric pressure in the storage environment of a glass cloth and a storage environment cumulative value determined by the number of days of storage satisfy the following conditional formula (a): (Tdp-14) × D ≦ 1500 (a) (In the formula, Tdp is the dew point under the atmospheric pressure of the storage environment, and D is the number of days of storage.) This includes producing a prepreg using the glass cloth that satisfies the above. If (Tdp-14) is a negative value, it is calculated as 0.

[0040] As an example, when a glass cloth is stored in an environment with a dew point (Tdp) of 18° C. for 30 days, then in an environment with a dew point (Tdp) of 24° C. for 30 days, and finally in an environment with a dew point (Tdp) of 10° C. for 30 days, the above formula (a) is expressed by the following formula: (18-14)x30+(24-14)x30+0x30=420 It is calculated as:

[0041] In the present disclosure, the "accumulated value of storage environment" is a value determined by the dew point under the atmospheric pressure of the storage environment and the number of days of storage, and refers to the value shown by formula (a) and formulas (b) to (e) described below. The accumulated value of the storage environment of the glass cloth can be controlled by controlling the dew point under the atmospheric pressure of the storage environment and / or the number of days of storage. In this context, the "number of days of storage" includes not only the number of days of the storage process, but also the number of days of various processes until the production of the prepreg is completed using the glass cloth. The completion of the production of the prepreg here means the point in time when the glass cloth is impregnated with the resin composition (i.e., the point in time when the above-mentioned <resin impregnation process> is completed).

[0042] The storage environment cumulative value is preferably represented by the following formula {preferably formula (b), more preferably formula (c), further preferably formula (d), particularly preferably formula (e)}: (Tdp-8)×D ≦800 (b) (Tdp-2)×D ≦800 (c) (Tdp-(-4))×D ≦1500 ···(d) (Tdp-(-10))×D ≦2300 ···(e) {In the formula, Tdp is the dew point of the glass cloth under the atmospheric pressure in the storage environment, and D is the number of days of storage. When (Tdp-8) in formula (b), (Tdp-2) in formula (c), (Tdp-(-4)) in formula (d), and (Tdp-(-10)) in formula (e) are negative values, they are calculated as 0.} Meet the following.

[0043] The above formula (a) can be further expressed as the following formula (a'): (Tdp-14)×D ≦800 ···(a´) It is preferable that the following is satisfied. The above formula (b) can be further expressed as the following formula (b´): (Tdp-8)×D ≦500 ···(b´) It is preferable that the following is satisfied. The above formula (c) can be further expressed as the following formula (c´): (Tdp-2)×D ≦500 ···(c´) It is preferable that the following is satisfied. The above formula (d) can be further expressed as the following formula (d´): (Tdp-(-4))×D ≦800 ···(d´) It is preferable that the following is satisfied. The above formula (e) can be further expressed as the following formula (e´): (Tdp-2)×D ≦1500 ···(e´) It is preferable that the following is satisfied. According to the above, it is easy to provide a method for producing a prepreg using a glass cloth that maintains excellent dielectric properties for a long period of time in an environment of less than 100°C.

[0044] <Storage period> The storage period of the glass cloth is controlled so that the cumulative value of the storage environment of the glass cloth satisfies the formula (a). From the viewpoints of securing the time required for transporting the glass cloth and improving the supply stability, the number of storage days is preferably 30 days or more, more preferably 90 days or more, even more preferably 180 days or more, even more preferably 365 days or more, and particularly preferably 730 days or more. From the viewpoints of reducing storage costs, the storage period of the glass cloth is preferably 5 years or less, more preferably 3 years or less. If the storage period is within the above range, the effect of controlling the cumulative value of the storage environment is easily obtained sufficiently. The longer the storage period, the more prominent the effect of suppressing the increase in the dielectric tangent is easily obtained.

[0045] From the viewpoint of having the necessary characteristics as a glass cloth for a prepreg of a printed wiring board, the "number of days of storage" for this purpose is counted from the time when both the process of thermally deoiling the glass cloth and the process of surface treating the glass cloth after thermal deoiling with a surface treating agent containing a silane coupling agent are completed. The starting point of counting the number of days of storage coincides with the starting point of measurement of the cumulative value of the storage environment. In addition, the "storage days" in this context is measured up to the day the glass cloth is processed into a prepreg. In other words, the end point of the "storage days" in this context is the day when the production of the prepreg is completed using the glass cloth, and may coincide with the end point of the "measurement period of the accumulated storage environment value." Note that, as described above, the completion of the production of the prepreg means the time when the glass cloth is impregnated with the resin composition (i.e., the time when the above-mentioned <resin impregnation process> is completed).

[0046] Regarding control of storage period, for example, Calculate the number of storage days that meets the range of the present disclosure, and use the glass cloth for prepreg production before the storage day is reached; and Monitoring the dew point of the storage environment of the glass cloth, calculating the cumulative value of the storage environment from time to time, and using the glass cloth for prepreg production while the dew point satisfies the range of the present disclosure; Methods such as the above may be adopted.

[0047] As an example, Storage at a given dew point for T1 days; Next, the glass cloth is heated and deoiled at a predetermined dew point, and then stored at the predetermined dew point for T2 days; Finally, the glass cloth is surface-treated under a predetermined dew point, and then stored under the predetermined dew point for T3 days; In such cases, the storage period is treated as T3. As a further example, in the case where a process for thermally degreasing the glass cloth is included but a process for surface treatment of the glass cloth is not included, the storage period is treated as T2.

[0048] From the viewpoint of easily obtaining a prepreg having a low dielectric tangent, the thermal deoiling step satisfies the following conditions (i) and (ii): (i) a step of degreasing the glass cloth by heating at a temperature of 600 to 1500° C. for a time of 10 minutes or less; and (ii) a step of degreasing the glass cloth by heating at a temperature of 300° C. or more and less than 600° C. for a period of 24 hours or more in an atmosphere having a dew point temperature of 15° C. or less under atmospheric pressure; That is, the prepreg is preferably produced using glass cloth that has been thermally deoiled and then stored under at least one of the above conditions (i) and (ii).

[0049] From the viewpoint of easily obtaining the effects of this embodiment, it is preferable to use the glass cloth for prepreg production preferably within 48 hours, more preferably within 24 hours, after being removed from the storage environment, for example, after being removed from the packaging material.

[0050] <Dew point> The dew point of the glass cloth under the atmospheric pressure of the storage environment is controlled so that the accumulated value of the glass cloth in the storage environment satisfies formula (a). The dew point of the glass cloth under the atmospheric pressure of the storage environment is preferably 18°C ​​dp or less. In this disclosure, unless otherwise specified, the dew point refers to the dew point under the atmospheric pressure of the storage environment. When the dew point is 18°C ​​dp or less, it is easy to prevent the dielectric tangent of the glass cloth from increasing over time. The dew point of the storage environment is preferably 13°C dp or less, more preferably 8°C dp or less, even more preferably 4°C dp or less or 0°C dp, even more preferably -4°C dp or less, and particularly preferably -10°C dp or less.

[0051] To control the dew point within the above range, known humidity control methods, humidity control media, humidity control mechanisms, and humidity control devices can be used, such as (1) using a moisture absorbent, (2) substituting the ambient atmosphere with a gas (e.g., dry gas) having a predetermined moisture content, (3) dehumidifying the ambient atmosphere using condensation at low temperatures, (4) reducing the pressure to adjust the ambient atmosphere to a predetermined moisture content, and (5) combinations of these.

[0052] The dew point can be controlled in an open or closed system, continuously or intermittently (regularly or irregularly), as long as the dew point is controlled within the above range. For example, the above controls (1) to (5) can be continuously performed in a closed system (e.g., in a sealed packaging material), intermittently performed in a closed system (e.g., only in seasons or weather days when the dew point is likely to rise), or continuously controlling the change in the dew point around the glass cloth in an open system. When the dew point is maintained by continuous humidity control, it is preferable to use a moisture absorbent, replacement with dry gas, a dehumidifier, or the like.

[0053] When a moisture absorbent is used to control the dew point, from the viewpoint of moisture absorption power, the moisture absorbent is preferably at least one selected from the group consisting of silica gel, calcium oxide, calcium chloride, calcined diatomaceous earth, synthetic zeolite, clay-based desiccant, phosphorus pentoxide, magnesium sulfate, copper sulfate, magnesium chloride, cobalt chloride, granular soda lime, and magnesium perchlorate. Among them, at least one selected from the group consisting of silica gel, calcium oxide, calcium chloride, and calcined diatomaceous earth is preferable. Also, from the viewpoint of occupied space and packaging form, it is preferable to use a sheet-shaped moisture absorbent.

[0054] It is preferable to use an appropriate amount of moisture absorbent depending on the moisture absorption capacity (amount of moisture absorbed and time of moisture absorption) of the moisture absorbent, the number of days of storage, etc. It is preferable to use a sufficient amount of moisture absorption. In other words, it is preferable that the maximum amount of moisture absorbent that the moisture absorbent can absorb is greater than the amount of moisture in the atmosphere. In addition, if the moisture absorbent is replaced periodically, it becomes easy to control the dew point.

[0055] When dry gas is used to control the dew point, it is preferable to use a gas (dry gas) having a dew point temperature of 18°C ​​dp or less. With such a dry gas, it is easy to control the dew point of the storage environment of the glass cloth. The dew point temperature of the dry gas is preferably 10°C dp or less, more preferably 0°C dp or less, even more preferably -10°C dp or less, even more preferably -20°C dp or less, and particularly preferably -30°C dp or less.

[0056] As the dry gas, for example, dry air having a dew point temperature range described above, or a gas containing at least one selected from the group consisting of nitrogen, argon, and oxygen having a dew point temperature range described above can be used. From the viewpoint of ease of handling, it is preferable to use dry air.

[0057] When a dehumidifier is used to control the dew point, examples of the dehumidifier include compressor types that utilize condensation at low temperatures and desiccant types (zeolite types) that repeatedly regenerate a dehumidifying agent using heat.

[0058] In order to suppress the change in the dew point over time, it is preferable to store the glass cloth in a sealed storage environment. As a sealing method, it is particularly preferable to suppress the inflow of moisture into the storage environment. A specific storage form will be described later. The dew point during the measurement period of the storage environment cumulative value may be controlled to remain constant or may fluctuate.

[0059] <Dew point and storage period> The number of days of storage in an environment with a dew point of 18°C ​​dp or more is preferably within 365 days, more preferably within 180 days, even more preferably within 60 days, and particularly preferably within 30 days. The number of days of storage in an environment with a dew point of 10°C dp or more is preferably within 365 days, more preferably within 180 days, even more preferably within 60 days, and particularly preferably within 30 days. The number of days of storage in an environment with a dew point of 5°C dp or more is preferably within 365 days, more preferably within 180 days, even more preferably within 60 days, and particularly preferably within 30 days. By controlling the number of days of storage in an environment with a dew point equal to or higher than a certain dew point within the above range, it is easy to suppress an increase in the dielectric tangent of the glass cloth over time.

[0060] <temperature> The glass cloth is preferably stored in an atmosphere in which the average temperature of the storage environment of the glass cloth is less than 100°C. When the average temperature is less than 100°C, it is easy to effectively suppress the increase in the dielectric tangent of the glass cloth over time. The average temperature of the glass cloth storage environment when storing the glass cloth is preferably 50°C or less, more preferably 40°C or less, even more preferably 35°C or less, even more preferably 30°C or less, and particularly preferably 25°C or less. The maximum temperature of the storage environment is preferably 400°C or less, more preferably 300°C or less, and even more preferably 200°C or less. The time during which the temperature of the storage environment is continuously 100°C or more and the maximum temperature or less is preferably less than 24 hours, more preferably less than 3 hours, and even more preferably less than 1 hour. Preferably, the temperature of the storage environment is controlled to be kept less than 100°C throughout the entire storage period. More preferably, the temperature is controlled to be 40°C or less, more preferably 35°C or less, even more preferably 30°C or less, and particularly preferably 30°C or less throughout the entire storage period. The temperature during the measurement period of the cumulative value of the storage environment may be controlled to remain constant or may fluctuate. If the temperature during the measurement period exceeds an expected value, the effect of the present invention is not impaired as long as the average temperature of the storage environment is less than 100°C.

[0061] <pressure> When reducing pressure to control the dew point, atmospheric pressure (10 5 It is preferable to control the pressure in the storage environment of the glass cloth to a reduced pressure of less than atmospheric pressure (Pa). A known reduced pressure control method, reduced pressure control medium, reduced pressure control mechanism, reduced pressure control device, etc. can be used as a method for controlling the pressure in the storage environment of the glass cloth to a reduced pressure of less than atmospheric pressure, and examples of the method include a vacuum pump.

[0062] The air pressure can be maintained by a known method as long as the storage environment of the glass cloth is maintained at a reduced pressure below atmospheric pressure. For example, the storage environment may be reduced in pressure continuously or intermittently (periodically or irregularly), or the glass cloth may be sealed in a packaging material whose pressure has been reduced to suppress changes in air pressure. The air pressure around the glass cloth when storing or packaging the glass cloth is preferably 104 Pa or less, more preferably 10 3 The atmospheric pressure during the measurement period of the storage environment cumulative value may be controlled to remain constant, or may be allowed to fluctuate.

[0063] <Storage form> Examples of the storage form of the glass cloth include storage in a room such as a storage room, storage in a packaging material, and a combination thereof. Examples of the packaging material include a box and a film. In each case, it is preferable to control the storage environment, i.e., the dew point, and optionally the average temperature and pressure of the atmosphere in direct contact with the glass cloth, within the above range. In addition, from the viewpoint of avoiding wrinkles in the glass cloth and reducing the storage space, it is preferable to store the glass cloth in a rolled state. In the rolled state, it is easy to minimize the area where the storage environment and the external environment come into contact and to reduce the internal volume during packaging, which makes it easier to more effectively suppress the increase in the dielectric tangent over time.

[0064] The storage chamber and packaging material for storing the glass cloth preferably have high sealing properties in terms of facilitating the maintenance of the dew point, temperature, and pressure. In addition to or instead of having high sealing properties, the storage chamber and packaging material are preferably configured to control the dew point inside (the storage environment). That is, the storage chamber and packaging material themselves preferably have the dew point control means as described above. Here, "sealed" means a state in which the opening is tightly closed without any gaps, thereby allowing the temperature, dew point, and air pressure in the storage environment of the glass cloth to be controlled below a certain standard. The "sealed state" means, for example, sealing to prevent the intrusion of solids, liquids, and gases. By suppressing the intrusion of solids, liquids, and gases, the effect of suppressing the increase in the dielectric tangent of the glass cloth is easily obtained.

[0065] When storing the glass cloth, it is preferable to wrap the glass cloth in a rolled state with a wrapping material. From the viewpoint of easily maintaining the dew point and temperature, it is preferable that the glass cloth is wrapped with a film and the opening is sealed. The sealing can be performed, for example, by thermocompression bonding the opening.

[0066] <Water vapor permeability> The packaging material has a water vapor permeability of 8g / (m2) at a measurement temperature of 40°C and a measurement humidity of 90%Rh. 2 With such a packaging material, it is easy to control the amount of moisture inside the packaging material and to suppress an increase in the dielectric tangent of the glass cloth over time due to the water present in the packaging material. From the viewpoint of easy control of the amount of moisture inside the packaging material, the water vapor transmission rate of the packaging material at a measurement temperature of 40°C and a measurement humidity of 90% Rh is preferably 8 g / (m 2 ×24hr) or less, more preferably 4g / (m 2 × 24hr) or less, more preferably 2g / (m 2 × 24hr) or less, and even more preferably 1g / (m 2 × 24hr), and particularly preferably 0.3 g / (m 2 ×24hr) or less, most preferably 0.1g / (m 2 ×24hr) or less. Water vapor permeability is 8g / (m 2 × 24 hr) or less, it is easy to suppress the amount of moisture that permeates, and therefore it is easy to control the amount of moisture inside the packaging material. The lower limit of the water vapor transmission rate may be 0 or may exceed 0.

[0067] <film> Films can also be used as packaging materials. There are no limitations on the type of film as long as the water vapor permeability falls within the above range, but examples of such films include ceramic vapor deposition films, aluminum vapor deposition films, aluminum foils, and aluminum laminate films. The thickness of the film is preferably 50 μm or more, more preferably 70 μm or more, further preferably 80 μm or more, and particularly preferably 90 μm or more. When the thickness is 50 μm or more, the water vapor permeability is likely to be small, and pinholes due to wrinkles, scratches, etc. are unlikely to occur.

[0068] <Box-shaped packaging material> The packaging material may be in the form of a box. Examples of packaging materials include those that have a water vapor transmission rate that satisfies the above range and have a specification that allows the opening to be sealed. Specific examples of packaging materials include metal, plastic, wood, and cardboard boxes, or boxes made by combining these. The "box" here refers to a movable, sealed container that isolates the glass cloth from the outside air, and multiple pieces of glass cloth may be stored therein.

[0069] [Prepreg] A further aspect of the present embodiment is a prepreg produced by the above-described production method. Such a prepreg is a composite of the above-mentioned glass cloth and a resin composition {containing an organic resin and, if necessary, optional components (inorganic particles and other components such as a crosslinking agent)}.

[0070] The above-mentioned glass cloth for producing the prepreg and the various raw materials for obtaining the same may be used alone or in combination of two or more kinds. The above-mentioned resin composition for producing the prepreg and the various raw materials for obtaining the same may be used alone or in combination of two or more kinds.

[0071] <Resin composition> The dielectric loss tangent of the cured resin composition at 10 GHz is preferably 0.0025 or less, more preferably 0.0020 or less, even more preferably 0.0018 or less, even more preferably 0.0014 or less, 0.0012 or less, and particularly preferably 0.0010 or less. If the dielectric loss tangent of the cured resin composition is within the above range, the dielectric loss tangent of the prepreg and the substrate can be easily reduced, and therefore, when a prepreg is produced using a glass cloth that suppresses an increase in the dielectric loss tangent, the effect of reducing the dielectric loss tangent can be easily obtained. Here, the term "cured product" includes not only products cured by chemical reactions (for example, crosslinking reactions) but also products cured by physical operations such as compressing and hardening a resin composition.

[0072] As the organic resin, either a thermosetting resin or a thermoplastic resin can be used. The thermosetting resin is preferably one or more selected from the group consisting of epoxy resin, allylated epoxy resin, maleimide resin, bismaleimide resin, cyanate resin, and cyclopentadiene-styrene copolymer resin. From the viewpoint of improving the dielectric properties of the resin substrate and from the viewpoint of easily ensuring the strength of the resin substrate, such a thermosetting resin can be suitably used.

[0073] The thermoplastic resin is preferably one or more thermoplastic resins selected from the group consisting of polyphenylene ether, polyether ether ketone, polyether ketone, polyether sulfone, and fluororesin. Among them, it is preferable to use fluororesin from the viewpoint of having excellent dielectric properties. The fluororesin is preferably at least one selected from the group consisting of polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), ethylene (Et)-TFE copolymer (ETFE), Et-chlorotrifluoroethylene (CTFE) copolymer, CTFE-TFE copolymer, TFE-HFP copolymer (FEP), TFE-PAVE copolymer (PFA), and polyvinylidene fluoride (PVdF).

[0074] <Inorganic particles and crosslinking agent> The prepreg may contain components other than the organic resin (other components) in the resin composition as necessary. Examples of the other components include inorganic particles and a crosslinking agent.

[0075] Examples of inorganic particles include those that can be added as fillers to resin compositions to enhance their heat resistance and flame retardancy. By including this type of filler, it is easy to further enhance heat resistance and flame retardancy. Specific examples of fillers include silica such as spherical silica, metal oxides such as alumina, titanium oxide, and mica, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, talc, aluminum borate, barium sulfate, and calcium carbonate. Among these, silica, mica, and talc are preferred as fillers, and spherical silica is more preferred. The fillers may be used alone or in combination of two or more. The fillers may be used as they are, or may be surface-treated with a silane coupling agent. Examples of the silane coupling agents include silane coupling agents having functional groups such as vinyl groups, styryl groups, methacryl groups, and acrylic groups in the molecule. In the case where a filler is contained, the content (filler content) is preferably 30 to 270 mass %, more preferably 50 to 250 mass %, based on the total weight of the resin composition. From the viewpoint of facilitating reduction of the dielectric loss tangent, it is preferable to use inorganic particles having a particularly low dielectric loss tangent value, for example, low dielectric silica powder.

[0076] As the crosslinking agent, any crosslinking agent capable of initiating or accelerating a crosslinking reaction can be used. From the viewpoint of excellent crosslinking reaction, the crosslinking agent preferably has an average of two or more unsaturated double bonds in one molecule. The crosslinking agent may be composed of one type of compound, or two or more types of compounds. Examples of the crosslinking agent include trialkenyl isocyanurate compounds such as triallyl isocyanurate (TAIC), trialkenyl cyanurate compounds such as triallyl cyanurate (TAC), multifunctional methacrylate compounds having two or more methacrylic groups in the molecule, multifunctional acrylate compounds having two or more acrylic groups in the molecule, multifunctional vinyl compounds having two or more vinyl groups in the molecule such as polybutadiene, vinylbenzyl compounds such as divinylbenzene having a vinylbenzyl group in the molecule, and multifunctional maleimide compounds having two or more maleimide groups in the molecule such as 4,4'-bismaleimide diphenylmethane. Among them, the crosslinking agent preferably contains at least one compound selected from the group consisting of triallyl cyanurate, triallyl isocyanurate, and polybutadiene.

[0077] [Substrates / Laminates] Another aspect of this embodiment means a resin plate (substrate) obtained by heating and pressurizing the prepreg. A resin plate obtained by stacking a plurality of prepregs and heating and pressurizing the prepregs is called a laminated plate, and the number of layers of the prepregs is not limited as long as the laminated plate described in the examples can be evaluated, but is preferably 1 to 20 layers, for example. After stacking the prepregs, heating and pressurization may be performed as necessary, for example, under the conditions described in the examples.

[0078] [Printed wiring board] Another aspect of this embodiment is a substrate formed by alternately stacking a plurality of metal layers for forming wiring on the prepreg, and applying heat and pressure. The number of wiring layers is not particularly limited, but 10 layers or more are preferable for high density wiring. Heating and pressure may be performed under conditions described in the examples, for example.

[0079] [Glass cloth manufacturing method] A further aspect of the present embodiment is a method for producing a glass cloth used in the above-mentioned method for producing a prepreg. The manufacturing method includes: A process of weaving glass yarns containing a plurality of glass filaments as warp yarns and weft yarns to obtain a glass cloth (weaving process); The method for producing the glass cloth includes the steps of: A step of thermally degreasing (heat cleaning) the glass yarn or glass cloth (thermal degreasing step); and a step of treating the glass yarn or glass cloth with a surface treatment agent (surface treatment step); The method for producing the glass cloth optionally includes: A process for opening the glass cloth (opening process); and A process of wrapping the glass cloth in a wrapping material (film and / or a box-shaped wrapping material) (wrapping process); It may further include at least one of the following.

[0080] <Weaving process> In the weaving process, the glass yarns are woven as warp and weft yarns to form a predetermined weaving structure. The preferred configuration and composition of the glass yarns and the weaving structure are as described above.

[0081] <Heat deoiling process> In the thermal deoiling step, the glass yarn or glass cloth is deoiled by heating. This step can be performed on the glass yarn or on the woven glass cloth. In other words, the step of weaving the glass yarn to obtain the glass cloth may be performed before, during, or after the thermal deoiling step. The thermal deoiling step can be performed by either (1) a method of deoiling the glass yarn or glass cloth (hereinafter, also simply referred to as "glass" in this step) at a relatively low temperature (e.g., less than 600°C) for a long period of time (e.g., 24 hours or more) or (2) a method of deoiling the glass at a relatively high temperature (e.g., 600 to 1600°C) for a long period of time or a short period of time (e.g., less than 24 hours).

[0082] (1) In the case of heating at a relatively low temperature, the temperature for thermal deoiling is preferably 100 to 500° C., more preferably 250 to 450° C., and even more preferably 350 to 450° C. The heating time for thermal deoiling in the case of (1) can be appropriately selected and is, for example, preferably 24 to 300 hours, more preferably 48 to 200 hours, and even more preferably 72 to 150 hours. When the combination of the thermal deoiling temperature and time is within the above ranges, the sizing agent adhering to the glass can be easily and sufficiently removed.

[0083] On the other hand, in the case of (2) heating at a relatively high temperature, the temperature of the thermal deoiling is preferably 600 to 1500°C, more preferably 800 to 1300°C, and even more preferably 900 to 1100°C. If the thermal deoiling temperature is 600°C or higher, organic substances such as the residue of the glue adhering to the glass can be easily removed sufficiently. Therefore, it is easy to lower the dielectric tangent of the glass cloth and to shorten the removal time. On the other hand, if the thermal deoiling temperature is 1500°C or lower, it is easy to suppress the devitrification phenomenon of the glass, and it is possible to effectively prevent the strength reduction of the glass cloth. In addition, the heating time in the thermal deoiling in the case of (2) can be appropriately selected, and is, for example, preferably 3 seconds or more and 72 hours or less, more preferably 3 seconds or more and 12 hours or less, even more preferably 3 seconds or more and 2 hours or less, particularly preferably 3 seconds or more and 10 minutes or less, and particularly preferably 3 seconds or more and 300 seconds or less.

[0084] From the viewpoint of easily obtaining a prepreg having a low dielectric tangent, the thermal deoiling is performed under the following conditions (i) and (ii): (i) a step of degreasing the glass cloth by heating at a temperature of 600 to 1500° C. for a time of 10 minutes or less; and (ii) a step of degreasing the glass cloth by heating at a temperature of 300° C. or more and less than 600° C. for a period of 24 hours or more in an atmosphere having a dew point temperature of 15° C. or less under atmospheric pressure; It is preferable that the above-mentioned method is carried out based on at least one of the above.

[0085] The heating means for thermal deoiling can be any known heating method, heating medium, heating mechanism, heating device, heating component, etc., as long as it is a method that can suitably control the thermal deoiling temperature. For example, it may be (1) a method of heating the glass in a heating furnace, (2) a method of bringing the glass into contact with a heating part, (3) a method of applying high-temperature steam to the glass, etc. Heating can be performed sequentially or continuously, in a closed system or an open system, or a combination of a closed system and an open system.

[0086] In the case of a closed system, it is preferable to place the glass in a heating furnace from the viewpoint of easy heating by a heating means, and in this case, it is preferable to heat the glass cloth while storing it in a rolled state from the viewpoint of storage space and heating range. It is also preferable to heat the glass while conveying it in the heating furnace from the viewpoint of increasing the efficiency of removing organic substances and shortening the time required for removing organic substances.

[0087] In the case of an open system, it is preferable to heat the glass while transporting it in a roll-to-roll manner from the viewpoint of the heated area. The glass can be transported by, for example, an unwinding mechanism and a winding mechanism.

[0088] The heating means of the heating furnace may be various means such as an electric heater or a burner, and a gas type single radiant tube burner or an electric heater is preferred. Heating may be performed by combining a plurality of means.

[0089] From the viewpoint of improving the heating efficiency, the heating furnace is preferably equipped with a means for discharging the gas generated in the heating furnace and / or an air circulation means. The gas discharge means may be a nozzle, a gas pipe, a small hole, a gas vent valve, etc. The air circulation means may be a fan, an air conditioning system, etc.

[0090] The heating furnace may be of either a batch type, which can house glass (e.g., a roll of glass cloth) and heat it at a predetermined atmospheric temperature, or a continuous type, which can heat the glass while continuously passing it through the heating furnace (e.g., heating while conveying it in a roll-to-roll manner). In order to efficiently remove organic matter adhering to the glass surface, the heating furnace is preferably of a continuous type. The above-mentioned heating furnace may be used as a method for heating the glass, but from the viewpoint of low running costs, the glass may be heated by contacting a member heated to a predetermined temperature with the glass.

[0091] The shape of the contact member is not particularly limited as long as it can heat the glass while suitably controlling the heating deoiling temperature, but a roll shape is preferred for ease of transporting the glass (heating roll method). As a member capable of heating glass in a roll shape, a roll that heats by induction heating is preferred, which can be used in high temperature ranges and has relatively little temperature variation in the width direction. When heating glass with a contact member, it is considered that the temperature of the contact member and the surface temperature of the glass are roughly the same.

[0092] As the glass is continuously heated, carbides may adhere to the heating roll. In order to remove the carbides adhering to the heating roll, the heating roll method is preferably provided with a mechanism for removing the adhering foreign matter, such as a blade.

[0093] Surface treatment process The surface treatment step can be performed on the glass yarn or on the woven glass cloth. In other words, the step of weaving the glass yarn to obtain the glass cloth may be performed before, during, or after the surface treatment step. The surface treatment process may be, for example, A step of attaching a silane coupling agent to the surface of the glass using a treatment liquid having a concentration of 0.1 to 0.5% by mass (coating step); A process of fixing the silane coupling agent to the glass surface by heating and drying (fixing process); These make it easier to suitably treat the surface of the glass.

[0094] Examples of the method for applying the treatment liquid to the glass in the coating step include (a) a method in which the glass is immersed or passed through the treatment liquid stored in a bath (hereinafter referred to as the "immersion method"); and (b) a method in which the treatment liquid is applied to the glass using a roll coater, a die coater, a gravure coater, or the like. When the immersion method is adopted, it is preferable to select the immersion time of the glass in the treatment liquid to be 0.5 seconds or more and 1 minute or less. When the immersion method is adopted, the glass can be passed through the treatment liquid at a conveying speed of 10 to 50 m / min while applying a predetermined tension (for example, 100 to 250 N) to the glass. After the treatment liquid is applied to the glass, the solvent contained in the treatment liquid can be heated and dried by a method such as hot air or electromagnetic waves. In order to make it easier to apply the surface treatment agent uniformly to the glass surface, it is preferable to squeeze the glass with a constant pressure using a rubber roller after immersing the glass in the surface treatment liquid.

[0095] The concentration of the surface treatment agent in the treatment liquid is preferably 0.1 to 0.5 mass %, more preferably 0.1 to 0.45 mass %, and even more preferably 0.1 to 0.4 mass %, based on the total mass of the treatment liquid, which facilitates more suitable surface treatment of glass.

[0096] In the fixing step, the heating and drying temperature is preferably 80° C. or higher, more preferably 90° C. or higher, so that the reaction between the silane coupling agent and the glass is sufficiently carried out, and is preferably 300° C. or lower, more preferably 180° C. or lower, so as to prevent deterioration of the organic functional group of the silane coupling agent.

[0097] <Opening process> The method for producing a glass cloth may further include the above-mentioned fiber-opening step. As a method for opening the glass cloth in this step, for example, a method of opening the glass cloth with spray water (high pressure water opening), a vibro washer, ultrasonic water, a mangle, or the like can be adopted. In most cases, the composition of the glass cloth does not usually change before and after the fiber-opening step.

[0098] <Packaging process> The method for producing the glass cloth may further include the above-mentioned packaging step. This makes it easier to control the storage environment of the glass cloth. Details of the packaging material are as described above. In the packaging step, it is preferable to control the dew point of the environment in direct contact with the glass cloth, and optionally the temperature, pressure, etc., to the storage environment of the present disclosure before packaging. The storage environment is as described above.

[0099] The above-mentioned steps do not necessarily have to be performed in a manner that can be distinguished as separate steps, and a plurality of steps can be performed together (simultaneously). The method for producing glass cloth can also include any steps other than the above-mentioned steps. For example, a slitting step can be included after the fiber-spreading step. If possible, the order of the above-mentioned steps can be changed. EXAMPLES

[0100] [Measurement and evaluation methods] <Method of measuring basis weight (mass of glass cloth)> The basis weight of the glass cloth was determined by cutting the glass cloth to a predetermined size and dividing the weight by the sample area. 2 The operation of cutting out pieces of this size and measuring their weight was repeated 10 times, and the average value was calculated as the weight per unit area.

[0101] <Method of measuring converted thickness> The glass cloth is a discontinuous planar body with air present between the glass fibers. Therefore, the converted thickness was calculated by dividing the basis weight of each glass cloth by the density of the glass. Specifically, the following formula: Converted thickness (μm) = basis weight (g / m 2 )÷Density(g / cm 3 ) The converted thickness was calculated by the above method. This converted thickness was used for the measurement by the resonance method.

[0102] <Method of measuring ignition loss> The ignition loss value of the glass cloth was measured in accordance with JIS R3420.

[0103] <Method for measuring dielectric tangent of glass cloth> The dielectric loss tangent of the glass cloth was determined in accordance with IEC 62562. Specifically, the glass cloth sampled to a size required for measurement with a split cylinder resonator was stored in a thermo-hygrostatic oven at 23°C and 50% RH for 8 hours or more (for example, about 18 hours). Then, the dielectric properties of the sample after storage were measured at 10 GHz using a split cylinder resonator (manufactured by EM Lab) and an impedance analyzer (manufactured by Agilent Technologies). The measurement was performed five times for one sample, and the average value obtained was calculated as the dielectric properties. The converted thickness was used as the thickness of the sample. Note that IEC 62562 mainly specifies a method for measuring the dielectric properties in the microwave band of fine ceramic materials used in microwave circuits.

[0104] <Method for measuring dielectric tangent of substrate and laminate> The substrate and laminate sampled to a size required for measurement with a cavity resonator were stored in a thermo-hygrostatic oven at 23°C and 50% RH for 8 hours or more (for example, about 18 hours). The dielectric properties of the samples after storage were measured at 10 GHz using a cavity resonator (manufactured by EM Lab) and an impedance analyzer (manufactured by Agilent Technologies). The measurement was performed five times for one sample, and the average value obtained was calculated as the dielectric properties. The thickness and width of the sample were measured using a micrometer. Specifically, a spindle was rotated and brought into contact with the measurement surface of the sample in parallel. The scale was read when the ratchet made three noises.

[0105] <Method for measuring dielectric tangent of cured resin composition> The cured resin composition sampled to a size required for measurement with a cavity resonator was stored in a thermo-hygrostatic oven at 23°C and 50% RH for 8 hours or more (for example, about 18 hours). The dielectric properties of the stored sample were measured at 10 GHz using a cavity resonator (manufactured by EM Lab) and an impedance analyzer (manufactured by Agilent Technologies). The measurement was performed five times for one sample, and the average value obtained was calculated as the dielectric properties. The thickness and width of the sample were measured using a micrometer. Specifically, a spindle was rotated and brought into contact with the measurement surface of the sample in parallel. The scale was read when the ratchet made three noises. The samples were prepared in the following manner.

[0106] <Method for producing a cured product of the resin composition of varnish A> The prepreg obtained by the method described in the Examples was loosened using Varnish A and passed through a 100 mesh sieve to obtain a powdered prepreg. The obtained powdered prepreg was placed in a mold with releasability and heated at 200°C and 31 kg / cm. 2 The resin composition was cured by heating and pressing at 400° C. for 120 minutes to obtain a cured product.

[0107] <Method for producing a cured product of the resin composition of varnish B> Microparticulated polytetrafluoroethylene (PTFE) was placed in a metal mold and heated to 380°C and 20 kg / cm 2 The mixture was heated and pressed at a pressure of 1000 MPa for 6 minutes to obtain a cured product of the resin composition.

[0108] <Method for producing a cured product of the resin composition of varnish C> The prepreg obtained by the method described in the Examples was loosened using Varnish C and passed through a 100 mesh sieve to obtain a powdered prepreg. The obtained powdered prepreg was placed in a mold with releasability and subjected to a pressure of 20 kg / cm under temperature conditions of 130°C for 15 minutes and 190°C for 80 minutes. 2The mixture was heated and pressed at a pressure of 1000 to obtain a cured product of the resin composition.

[0109] <Methods for measuring temperature and dew point, and for recording the number of days> The temperature and dew point were measured using a Vaisala handheld dew point meter DM70. Depending on the dew point to be measured, the DMP74A or DMP74B probe and the MI70 indicator were used to measure the dew point under the atmospheric pressure of the storage environment. Specifically, the DMP74A probe was used when the dew point was above -30°C dp, and the DMP74B probe was used when the dew point was below -30°C dp. The temperature and dew point were measured every 3 hours using the DM70. The average value of the measured temperature (average temperature) was calculated. The period (number of days) during which the dew point was shown was also recorded.

[0110] <Pressure measurement method> The pressure inside the box was measured by visually reading a pressure gauge attached to the box.

[0111] <Method for measuring water vapor permeability of packaging materials> A: For packaging materials with a thickness of 2 mm or less, such as plastic films, plastic sheets, and multi-layer materials containing plastics The thickness and water vapor permeability of the packaging material were measured in accordance with JIS K7130 and JIS K7129-1. The measurement was performed three times for one sample, and the average values ​​obtained were calculated as the thickness and water vapor permeability of the packaging material. The test pieces used were visually free of wrinkles, folds, and pinholes and had a uniform thickness. The measurement conditions were as follows. Measurement conditions Equipment: Water vapor transmission meter L80-5000 (Lyssy ISO-PE-Z91) Thickness gauge: ID-C1012C (Mitutoyo ISO-PE-Z78) ·Temperature / Humidity: 40℃・90%Rh ·Measurement area: approx. 50cm 2 Reference sample: PET 19μm thickness {25.5g / (m 2×24hr) Measurement direction: Through the glass cloth from the outer surface of the packaging

[0112] <B: When packaging materials are not subject to A> For packaging materials other than those covered by "A" above, the temperature is 40°C, the humidity outside the packaging is adjusted to 90% Rh, and the air inside is kept dry and sealed. The weight of water vapor that penetrates into the packaging is measured, and the weight of water vapor that penetrates into the packaging is calculated per 24 hours and per square meter of the external surface area of ​​the packaging. 2 The calculation was based on the hit rate.

[0113] Specifically, dry air with a dew point of -30℃dp was enclosed in the packaging material, and 800g of moisture absorbent of JIS Z 0701 (packaging desiccant) Class 1A or equivalent quality was also placed inside, at which point the temperature and dew point were measured and the material was sealed. If it was not possible to fit 800g of moisture absorbent, the weight of the moisture absorbent was measured and the moisture absorbent was placed in a volume that was more than half the volume of the packaging material.

[0114] Next, the sealed packaging material was placed in a thermo-hygrostat at 40°C and 90% Rh, and the packaging material was stored in the thermo-hygrostat for an appropriate time of 48 hours or more (for example, about 72 hours). After a certain time (this time is called the retention time in the thermo-hygrostat), the packaging material was removed from the thermo-hygrostat, and the temperature and dew point inside the packaging material and the post-test weight of the moisture absorbent were immediately measured. If the post-test weight of the moisture absorbent exceeded 130% of the weight of the enclosed moisture absorbent, the retention time in the thermo-hygrostat was shortened or the amount of moisture absorbent was increased, and the measurement was repeated. In addition, the absolute humidity (g / m) before and after the test was calculated from the temperature and dew point measured before and after the test. 3 Specifically, the temperature and dew point were input into the VAISALA Humidity Calculator, and the absolute humidity was calculated. The measurement was performed three times for one sample, and the absolute humidity was calculated using the following formula: Change in water vapor volume (g) = {absolute humidity at end of test (g / m 3 )-Absolute humidity at the start of the test (g / m3 )}×Inner volume of packaging material (m 3 ) Water vapor permeability {g / (m 2 × 24hr)}={Weight of moisture absorbent after test (g) - Weight of moisture absorbent enclosed (g) + Change in water vapor amount (g)} / [External surface area of ​​packaging material (m 2 )×{Holding time in constant temperature and humidity device (hr) / 24(hr)}] The water vapor permeability was calculated using the above formula, and the average value was calculated as the water vapor permeability.

[0115] <Change rate of dielectric tangent (Df) of glass cloth> The rate of change in the dielectric tangent (Df) of the glass cloth is the dielectric tangent (Df 0 ) after a measurement period of X days. x ) to the following formula: Df change rate (%) = (Df x / Df 0 ) x 100 It was calculated by:

[0116] The smaller the rate of change (increase) of the dielectric loss tangent at 10 GHz over a long period of time, the greater the effect of controlling the cumulative value of the storage environment of the glass cloth. The rate of change of the glass cloth over time is evaluated by the above formula, and this rate of change is preferably 180% or less or 170% or less, more preferably 160% or less, 140% or less or 120% or less, even more preferably 110% or less, and particularly preferably 105% or less.

[0117] [Manufacturing of grey cloth] <Production of Q1035> SiO 2A cloth was woven using an air jet loom with a weaving density of 66 warp threads / 25 mm and 68 weft threads / 25 mm using glass yarns with a composition content of more than 99.9% by mass. The cloth was woven to a width of 1300 mm. As the warp threads, silica glass yarns with an average filament diameter of 5.0 μm, 100 filaments, and 1.0Z twist were used. As the weft threads, silica glass yarns with an average filament diameter of 5.0 μm, 100 filaments, and 1.0Z twist were used.

[0118] <Production of L1035> SiO 2 The composition amount is 53 mass%, and B 2 O 3 A cloth was woven using an air jet loom with a composition amount of 23% by mass of glass yarn and a weaving density of 66 warp yarns / 25 mm and 68 weft yarns / 25 mm. The cloth width was 1300 mm. As the warp yarn, a glass yarn with an average filament diameter of 5.0 μm, 100 filaments, and 1.0Z twist was used. As the weft yarn, a glass yarn with an average filament diameter of 5.0 μm, 100 filaments, and 1.0Z twist was used.

[0119] [Varnish manufacturing] <Varnish A> A varnish was prepared with a blending ratio of 70 parts by mass of modified PPE (SABIC Innovative Plastics, trade name: SA9000, weight average molecular weight Mw2000, number of terminal functional groups 2), 30 parts by mass of TAIC (triallyl isocyanurate, Nippon Kasei, molecular weight 249, number of terminal double bonds 3), 100 parts by mass of silica filler (Admatechs, trade name: SC2300-SVJ), and 0.5 parts by mass of PBP {1,3-bis(butylperoxyisopropyl)benzene, NOF Corp., trade name: Perbutyl P}. Toluene and other than the silica filler were mixed so that the solid content concentration was 60% by mass, and the silica filler was further mixed at the timing when the solid content was dissolved in toluene. The mixture was stirred until the silica filler was uniform, and varnish A was obtained. The obtained varnish was used to prepare a cured product according to the above-mentioned <Method for preparing a cured product of the resin composition of varnish A>, and various measurements were then carried out according to the above-mentioned <Method for measuring the dielectric tangent of the cured product of the resin composition>. As a result, the dielectric tangent of the cured product of the resin composition of varnish A was 0.0018 at 10 GHz.

[0120] <Varnish B> Varnish B was prepared with a blend ratio of 60% by mass of microparticulated polytetrafluoroethylene (PTFE), 6% by mass of nonionic surfactant, and 34% by mass of distilled water. After preparing a cured product of varnish B by the above-mentioned <Method of preparing a cured product of the resin composition>, various measurements were performed according to the above-mentioned <Method of measuring the dielectric tangent of the cured product of the resin composition>. As a result, the dielectric tangent of the cured product of the resin composition of varnish B was 0.0002 at 10 GHz.

[0121] <Varnish C> A varnish was prepared with a blend ratio of 100 parts by mass of phenol-dicyclopentadiene type epoxy resin (manufactured by DIC Corporation, product name: HP-7200H), 37.5 parts by mass of phenol novolac resin (manufactured by AICA Corporation, product name: Shounol BRG-557), and 2E4MZ: 2-ethyl-4-methylimidazole (manufactured by Shikoku Kasei Corporation, product name: Curesol 2E4MZ). Varnish C was obtained by mixing and stirring with methyl ethyl ketone (MEK) so that the solid content concentration was 60% by mass. After preparing a cured product of varnish C according to the above-mentioned <Method of preparing a cured product of the resin composition>, various measurements were performed according to the above-mentioned <Method of measuring the dielectric tangent of the cured product of the resin composition>. As a result, the dielectric tangent of the cured product of the resin composition of varnish C was 0.0021 at 10 GHz.

[0122] [Examples and Comparative Examples] Example 1 The obtained Q1035 greige cloth was heated in a heating furnace at 600° C. for 60 seconds to carry out deoiling (thermal deoiling process).

[0123] Next, 0.15% by mass of 3-methacryloxypropyltrimethoxysilane (silane coupling agent A); Z6030 (manufactured by Dow Toray Co., Ltd.) and 0.15% by mass of 5-hexenyltrimethoxysilane (silane coupling agent B); Z6161 (manufactured by Dow Toray Co., Ltd.) were dispersed in pure water adjusted to pH = 3 using acetic acid, thereby preparing a treatment solution. The cloth was immersed in the treatment solution at a line tension of 200 N and a line speed of 30 m / min (surface treatment agent application process), and after squeezing the liquid with a pressure of 0.3 MPa using an NBR rubber roll, it was heated and dried at 130 °C for 60 seconds, thereby fixing the silane coupling agent (fixing process). The dried cloth was sprayed with 2.0 kg / cm 2 After high pressure spreading, the glass cloth was dried at 130°C for 1 minute (drying step) and then wound up to obtain a roll of glass cloth.

[0124] Within 3 hours after the surface treatment, the glass cloth was placed in a stainless steel box (water vapor permeability 0.0 g / (m)) in an environment with a temperature of 30°C and a dew point of 24°C. 2× 24 hr) and then evacuate the inside of the container for 10 min using a vacuum pump. 3 The pressure was reduced to 10 Pa.

[0125] The glass cloth was then sealed, moved to an external environment with a temperature of 23° C. and a dew point of 19° C. dp, and stored for 720 days. At this time, the dew point inside the box-shaped packaging material was −30° C. dp. After 720 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage.

[0126] For glass cloth after storage, within 3 hours after removal, 1) After storage, the glass cloth is immersed in varnish A and then impregnated with varnish A; 2) After storage, the excess varnish on the glass cloth is scraped off by passing the glass cloth through a specified slit; and 3) After storage, the glass cloth is dried at 95°C for 5 minutes to remove any solvent remaining on the glass cloth after storage; As a result, a prepreg was obtained.

[0127] As described above, in this example, after the storage process lasted for 720 days, the glass cloth was taken out and the prepreg production was completed on the same day. Therefore, the storage period (measurement period for the cumulative storage environment value) in this example was 720 days.

[0128] Four sheets of the obtained prepreg were stacked and heated at 200°C and 31 kg / cm 2 The mixture was heated and pressed at 40° C. for 120 minutes. This resulted in a laminate having a cured resin composition. The volume fraction of the resin composition in the resulting laminate was 50%.

[0129] Example 2 A roll-shaped glass cloth was obtained in the same manner as in Example 1, except that the conditions for the thermal deoiling of the obtained Q1035 greige cloth were changed as shown in the table below. Within 3 hours after the surface treatment, this glass cloth was wrapped in an aluminum laminate film {thickness 99 μm, water vapor permeability 0.1 g / (m)} in an environment of a temperature of 23°C and a dew point of 12°C dp. 2× 24 hr) bag and 800 g of a moisture absorbent {Abrio (registered trademark) AW (A-type silica gel) manufactured by Toyoda Chemical Industries, Ltd.} was enclosed inside. Furthermore, the opening was heat-pressed and sealed.

[0130] Thereafter, the glass cloth was moved to an external environment with a temperature of 30°C and a dew point of 24°C dp, and stored for 720 days. At this time, the dew point inside the film bag was -8°C dp. After 720 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. Using the obtained glass cloth after storage, a prepreg and a laminate were obtained in the same manner as in Example 1.

[0131] Example 3 A roll-shaped glass cloth was obtained in the same manner as in Example 1, except that the conditions for the thermal de-oiling of the obtained Q1035 greige cloth were changed as shown in the table below, and a treatment liquid was prepared by dispersing 0.30 mass% of 3-methacryloxypropyltrimethoxysilane (silane coupling agent A); Z6030 (manufactured by Dow Toray Industries, Inc.) in the treatment liquid.

[0132] Within 3 hours after the surface treatment, the glass cloth was placed in a storage room controlled at a temperature of 30° C. and a dew point of −4° C. dp, and stored for 365 days. After 365 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage.

[0133] For glass cloth after storage, within 3 hours after removal, 1) After storage, the glass cloth is immersed in varnish C and then impregnated; 2) After storage, the excess varnish on the glass cloth is scraped off by passing the glass cloth through a specified slit; and 3) After storage, the glass cloth is dried at 130°C for 7 minutes to remove any solvent remaining on the glass cloth after storage; As a result, a prepreg was obtained.

[0134] Four sheets of the obtained prepreg were stacked and subjected to temperature conditions of 130°C for 15 minutes and 190°C for 80 minutes, and then subjected to a compression test of 20 kg / cm 2A laminate having a cured resin composition was obtained by heating and pressing at a pressure of 1000 MPa. The volume fraction of the resin composition in the obtained laminate was 50%.

[0135] Example 4 The rolled glass cloth obtained in Example 1 was placed in a storage room controlled at a temperature of 25°C and a dew point of 0°C dp using a dehumidifier within 3 hours after the surface treatment, and stored for 365 days. After 365 days, the glass cloth was taken out, and a part of it was used to evaluate the glass cloth after storage.

[0136] For glass cloth after storage, within 3 hours after removal, 1) After storage, the glass cloth is immersed in varnish B and allowed to soak; 2) After storage, the excess varnish on the glass cloth is scraped off by passing the glass cloth through a specified slit; and 3) After storage, the glass cloth is dried at 130°C for 7 minutes to remove any solvent remaining on the glass cloth after storage; As a result, a prepreg was obtained.

[0137] One piece of the obtained prepreg was heated at 380°C and 20 kg / cm 2 The substrate was heated and pressed for 6 minutes at a pressure of 1000 MPa to obtain a substrate having a cured resin composition. The volume fraction of the resin composition in the substrate was 50%.

[0138] Example 5 The rolled glass cloth obtained in Example 1 was placed in a storage room maintained at a temperature of 25°C and a dew point of 4°C dp using a dehumidifier within 3 hours after the surface treatment, and stored for 365 days. After 365 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. Using the obtained glass cloth after storage, a prepreg and a laminate were obtained in the same manner as in Example 1.

[0139] Example 6 The rolled glass cloth obtained in Example 1 was stored for 365 days in a storage room maintained at a temperature of 25°C and a dew point of 9°C dp using a dehumidifier within 3 hours after the surface treatment. After 365 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. A prepreg and a laminate were obtained using the obtained glass cloth after storage in the same manner as in Example 1.

[0140] Example 7 The rolled glass cloth obtained in Example 1 was placed in a storage room maintained at a temperature of 25°C and a dew point of 14°C dp within 3 hours after the surface treatment and stored for 310 days. After 310 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. A prepreg and a laminate were obtained using the obtained glass cloth after storage in the same manner as in Example 1.

[0141] Example 8 The rolled glass cloth obtained in Example 1 was placed in a storage room maintained at a temperature of 25°C and a dew point of 19°C dp within 3 hours after the surface treatment and stored for 270 days. After 270 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. Using the obtained glass cloth after storage, a prepreg and a laminate were obtained in the same manner as in Example 1.

[0142] Example 9 The rolled glass cloth obtained in Example 1 was placed in a storage room maintained at a temperature of 25°C and a dew point of 16°C dp within 3 hours after the surface treatment and stored for 30 days. After 30 days, the temperature of the storage room was changed to 25°C and the dew point was 3°C dp, and the glass cloth was taken out after 335 days, i.e., after a total of 365 days, and a part of it was used to evaluate the glass cloth after storage. Using the obtained glass cloth after storage, a prepreg and a laminate were obtained in the same manner as in Example 1.

[0143] Comparative Example 1 The rolled glass cloth obtained in Example 1 was placed in a storage room maintained at a temperature of 25°C and a dew point of 20°C dp within 3 hours after the surface treatment and stored for 720 days. After 720 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. Using the obtained glass cloth after storage, a prepreg and a laminate were obtained in the same manner as in Example 1.

[0144] Comparative Example 2 The rolled glass cloth obtained in Example 2 was placed in a storage room maintained at a temperature of 30°C and a dew point of 24°C dp within 3 hours after the surface treatment and stored for 365 days. After 365 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. Using the obtained glass cloth after storage, a prepreg and a laminate were obtained in the same manner as in Example 1.

[0145] Comparative Example 3 The rolled glass cloth obtained in Example 3 was placed in a storage room maintained at a temperature of 30°C and a dew point of 24°C dp within 3 hours after the surface treatment and stored for 365 days. After 365 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. Using the obtained glass cloth after storage, a prepreg and a laminate were obtained in the same manner as in Example 1.

[0146] <Reference example> A roll-shaped glass cloth was obtained in the same manner as in Example 1, except that the obtained L1035 green cloth was heated at 370°C for 72 hours using a batch-type heating furnace as a thermal deoiling process. This glass cloth was placed in a storage room maintained at a temperature of 25°C and a dew point of 20°C dp within 3 hours after the surface treatment process and stored for 720 days. After 720 days, the glass cloth was taken out and a part of it was used to evaluate the glass cloth after storage. A prepreg and a laminate were obtained in the same manner as in Example 1 using the obtained glass cloth after storage.

[0147] The production conditions and evaluation results for the examples and comparative examples are shown in the table below. [Table 1]

[0148] [Table 2]

[0149] In the examples, it was confirmed that excellent dielectric properties could be maintained for a long period of time in an environment below 100°C. On the other hand, in the comparative examples, the dielectric loss tangent of the glass cloth increased significantly after storage, and as a result, the dielectric loss tangent of the prepreg produced, and in turn, the dielectric loss tangent of the laminate also increased significantly. In the reference examples using glass cloth that does not fall under the category of low dielectric glass, no increase in the dielectric loss tangent was observed even in the same storage environment as in the comparative examples.

Claims

1. A method for producing a prepreg, comprising the steps of impregnating a glass cloth with a resin composition and producing a prepreg, The glass cloth may include The following condition formula (a): (Tdp-14)×D≦1500...(a) (In the formula, Tdp is the dew point under the atmospheric pressure of the storage environment, and D is the number of days of storage.) and the glass cloth has a dielectric loss tangent of 0.00200 or less at 10 GHz after storage. A method for producing prepreg.

2. The glass cloth has glass yarns containing a plurality of filaments as warp yarns and weft yarns, The silicon (Si) content in the glass yarn is silicon dioxide (SiO 2 The method for producing a prepreg according to claim 1, wherein the total mass of the prepreg is 95.0 to 100 mass% in terms of mass per unit area.

3. The glass cloth may include The following conditional formula (b): (Tdp-8)×D≦800...(b) The method for producing a prepreg according to claim 1 or 2, wherein the prepreg is produced using the glass cloth stored under conditions that satisfy the above.

4. The glass cloth may include The following condition formula (c): (Tdp-2)×D≦800...(c) The method for producing a prepreg according to claim 3, wherein the prepreg is produced using the glass cloth stored under conditions that satisfy the above.

5. The glass cloth may include The following condition formula (d): (Tdp-(-4))×D≦1500...(d) The method for producing a prepreg according to claim 4, wherein the prepreg is produced using the glass cloth stored under conditions that satisfy the above.

6. The following conditions (i) and (ii): (i) degreasing the glass cloth by heating at a temperature of 600 to 1500° C. for a time of 10 minutes or less; and (ii) a step of degreasing the glass cloth by heating at a temperature of 300° C. or more and less than 600° C. for 24 hours or more in an atmosphere having a dew point temperature of 15° C. or less under atmospheric pressure; The method for producing a prepreg according to claim 1 or 2, wherein the prepreg is produced using the glass cloth that has been heated and deoiled according to at least one of the above and then stored.

7. The following formula (1): X (R) 3-n Yes n ・・・(1) (In the formula, X is a group having at least one of an amino group and an unsaturated double bond group having radical reactivity, each Y is independently an alkoxy group, n is an integer of 1 to 3, and each R is independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group.) The method for producing a prepreg according to claim 1 or 2, wherein the prepreg is produced using the glass cloth that has been surface-treated with a surface treatment agent containing the silane coupling agent represented by the formula (I) and then stored.

8. The method for producing a prepreg according to claim 1 or 2, wherein a cured product of the resin composition has a dielectric loss tangent of 0.0025 or less at 10 GHz.

9. 3. The method for producing a prepreg according to claim 1 or 2, wherein the resin composition contains at least one resin selected from the group consisting of epoxy resins, allylated epoxy resins, maleimide resins, bismaleimide resins, cyanate resins, cyclopentadiene-styrene copolymer resins, polyphenylene ethers, polyetheretherketones, polyetherketones, polyethersulfones, and fluororesins.

10. The method for producing a prepreg according to claim 1 or 2, wherein the resin composition contains at least one of inorganic particles and a crosslinking agent.

11. The glass cloth may include 3. The method for producing a prepreg according to claim 1 or 2, wherein the glass cloth has a dielectric loss tangent of 0.00200 or less at 10 GHz both before and after storage under conditions that satisfy the conditional formula (a).

12. The glass cloth may include 3. The method for producing a prepreg according to claim 1 or 2, wherein the glass cloth has a rate of change in dielectric tangent before and after storage (dielectric tangent at 10 GHz after storage under conditions satisfying said conditional formula (a) / dielectric tangent at 10 GHz before storage under conditions satisfying said conditional formula (a)) of 180% or less.

13. The method for producing a prepreg according to claim 1 or 2, further comprising the steps of heating and drying the glass cloth impregnated with the resin composition.

14. A method for producing a prepreg for a printed wiring board, comprising producing the prepreg according to claim 1 or 2 for a printed wiring board.

Citation Information

Patent Citations

  • Glass fiber drying and placing device

    CN213137446U

  • Prepreg preservation method, laminate, and laminate packaging material

    JP2014091782A

  • Annealed quartz glass cloth and manufacturing method thereof

    JP2021195689A

  • Quartz glass cloth manufacturing method

    JP7269416B1

  • Quartz glass cloth packaging method

    JP7375902B1